Quality of public spaces in land subdivisions implemented through partnerships - Pereira , Isabela Oliveira; Bezerra, Maria do Carmo de Lima (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The paper conducts a study on urban regulation aimed at defining the quality of urban public spaces to promote the quality of urban life. The analyzed urban instrument is the land subdivision law and its various changes that have occurred over the years, since 1979. The analysis focuses on the recent changes carried out by Law No. 13,465/17 (Lei n° 13.465/17), which introduces the land subdivision modalities: controlled access allotments and condominium of lots, related to the management of public space by private agents. The objective is to assess whether the urban requirements demanded at the local level for these subdivision modalities have contributed to better urban spaces and to a management that guarantees adequate maintenance. As a method, it uses a comparative analysis of Law No. 6,766/79 (Lei n° 6.766/79) and the various changes that have occurred, regarding the urban requirements for the constitution of public spaces and their management, verifying the role of the federal government and local governments in this area. Based on this analysis, it carries out an empirical study of the project ’Cidade Urbitá’, to be implemented in Brasília/DF, assessing the possibility that it will result in dynamic public spaces. As a contribution, recommendations are made, which could be adopted by municipalities when preparing municipal regulations in favor of public spaces that promote more dynamic urban life.